Application of Time-of-Flight (ToF) Laser Sensor for Real-Time Cutting Width Monitoring System on Mini Combine Harvester - Renny Eka Putri; J P Geraldo; Andasuryani Andasuryani (The University of Lampung, 2023)
Yield monitoring is a precision farming technology that monitors crop yields in real-time. The cutting width is one of the variables gathered by yield monitoring. The cutting width is measured using the sensor by subtracting the width of the header from a distance reading from the sensor to the rice installed on the left and right sides of the mini combine harvester header. This research aims to design a cutting width measurement system using the VL53L1X ToF sensor on a mini combine harvester. The VL53L1X ToF Sensor is used as a distance sensor, followed by an ESP-32 microcontroller and a WiFi module. These are linked to the database and interpreted into digital form using an I 2 C LCD so that the user may see the results afterward. The accuracy of the two sensors (left and right) is evaluated by comparing distance measurement results on an object with an R 2 value of 1. For static testing on rice plants (Oryza sativa L), ten data collecting variations with three repetitions were conducted, with an average R2 of 0.9975 throughout the three repetitions. The dynamic test system includes an Ublox GPS tracker used to read coordinates for variability mapping of cutting width on ArcGIS application using the kriging method. The kriging result shows five different cutting width classes and the difference in variability in harvesting on the field. Keywords: Sensor, Mini Combine Harvester, Accuracy, Cutting Width